An Interdisciplinary Exploration of Moral Distress in Healthcare Providers (HCPs) Caring for Patients Requiring Long-term Ventilation - Mcloughlin, Paul (Université d'Ottawa | University of Ottawa, 2025)
Introduction – Moral engagements are a deeply inherent and intractable component of modern healthcare practice. Challenges arise when there are multiple core values conflicting, often in an emotionally charged, confusing, and at times frightening environment. These challenges affect not only healthcare providers (HCPs) but also patients and their loved ones, healthcare organizations, and the wider community. When these ethical uncertainties, conflicts, and dilemmas are unable to be resolved satisfactorily moral suffering ensues. Moral distress is a particular form of moral suffering. Moral distress is defined as the suffering experienced because of situations in which HCPs are aware of a moral problem, assume moral responsibility for the issue, and subsequently make a moral judgment as to what they believe is the right word or action to take (or not take). However, due to internal or external constraints, real or perceived, the HCP feels they cannot act on their beliefs. The HCP then sees themselves as compromising their personal and/or professional values resulting in the phenomenon of moral distress. This moral distress may be experienced as guilt, shame, helplessness, anger, frustration, and powerlessness. There is a significant correlation between moral distress and the HCP’s emotional, physical, and spiritual well-being. Purpose of research – The purpose of this research is to explore the phenomenon of moral distress, through an interdisciplinary research lens, looking at the whole multidisciplinary team caring for patients requiring long-term ventilatory support. These HCPs were drawn from the disciplines of nursing, clinical management, medicine, pharmacy, respiratory therapy, physiotherapy, spiritual care, and social work. This study is unique in exploring moral distress in this population and environment. There are many shared sequelae, symptoms, and concepts, such as powerlessness, shame, helplessness, courage, guilt, forgiveness, and non-acceptance, in the moral suffering of the alcoholic and the moral suffering of the HCP. What insights might we learn from the sufferer recovering from alcoholism who is practicing 12 Step spirituality and the HCP living with moral distress? The possible application of 12 Step spiritual principles and practices in dealing with and healing from moral distress will be explored. Deepening our understanding of moral distress may be crucial in developing effective remedies to mitigate the causes of moral distress, facilitate healing, and promoting moral resilience in our HCPs and healthcare organizations. Thus, the participants were encouraged to share their experience not only of moral distress but also how they personally made sense of and dealt with moral distress. Furthermore, they were given space to provide answers to what works at an organizational level to mitigate, process, and heal from moral distress. Methodology – An interpretative phenomenological research method was employed. This method allowed an in-depth exploration of the HCPs’ lived experience and parallels in literature with the interdisciplinary research method. It was a method ideally suited to exploring the issue of moral distress through the subjective lived experience of the phenomenon. The Measure of Moral Distress for Healthcare Professionals (MMD-HP) validated questionnaire was completed and in-depth interviews undertaken to obtain a clear understanding of the person’s lived experience of the phenomenon of moral distress. Findings & Discussion – Multiple professional perspectives were obtained from the HCPs working on the unit. Two of the HCPs left the unit due to moral distress. Their testimony was rich, powerful, and furthers our understanding of moral distress in these various healthcare professions. Evidence informed personal and organizational suggestions, based on the HCP’s lived experience, are offered for dealing with and healing from moral distress. This research uniquely uncovers and highlights the epistemological and ontological difference between powerlessness and helplessness as experienced by HCPs on a long-term ventilation unit. It will be vital that we differentiate between these two concepts when discussing and treating moral distress in HCPs.
Keywords: Moral Distress; Moral Injury; Spirituality; Interpretative Phenomenological Analysis; Long-term Ventilation; Chronic Vent